Urinary bladder partial carbon dioxide tension during hemorrhagic shock and reperfusion: an observational study - Dubin, Arnaldo (2005)
Introduction: Continuous monitoring of bladder partial carbon dioxide tension (PCO₂) using fibreoptic sensor technology may represent a useful means by which tissue perfusion may be monitored. In addition, its changes might parallel tonometric gut PCO₂. Our hypothesis was that bladder PCO₂, measured using saline tonometry, will be similar to ileal PCO₂ during ischaemia and reperfusion. Method: Six anaesthetized and mechanically ventilated sheep were bled to a mean arterial blood pressure of 40 mmHg for 30 min (ischaemia). Then, blood was reinfused and measurements were repeated at 30 and 60 min (reperfusion). We measured systemic and gut oxygen delivery and consumption, lactate and various PCO₂ gradients (urinary bladder–arterial, ileal–arterial, mixed venous–arterial and mesenteric venous–arterial). Both bladder and ileal PCO2 were measured using saline tonometry. Results: After bleeding systemic and intestinal oxygen supply dependency and lactic acidosis ensued, along with elevations in PCO₂ gradients when compared with baseline values (all values in mmHg; bladder ∆PCO₂ 3 ± 3 versus 12 ± 5, ileal ∆PCO₂ 9 ± 5 versus 29 ± 16, mixed venous–arterial PCO₂ 5 ± 1 versus 13 ± 4, and mesenteric venous–arterial PCO₂ 4 ± 2 versus 14 ± 4; P < 0.05 versus basal for all). After blood reinfusion, PCO₂ gradients returned to basal values except for bladder ∆PCO₂, which remained at ischaemic levels (13 ± 7 mmHg). Conclusion: Tissue and venous hypercapnia are ubiquitous events during low flow states. Tonometric bladder PCO₂ might be a useful indicator of tissue hypoperfusion. In addition, the observed persistence of bladder hypercapnia after blood reinfusion may identify a territory that is more susceptible to reperfusion injury. The greatest increase in PCO₂gradients occurred in gut mucosa. Moreover, the fact that ileal ∆PCO₂ was greater than the mesenteric venous–arterial PCO₂ suggests that tonometrically measured PCO₂ reflects mucosal rather than transmural PCO₂. Ileal ∆PCO₂ appears to be the more sensitive marker of ischaemia.